2017
DOI: 10.1007/7355_2016_27
|View full text |Cite
|
Sign up to set email alerts
|

Isoform Selective PI3K Inhibitors for Treating Cancer

Abstract: The PI3K/AKT pathway is one of the most frequently altered in cancer and several promising small-molecule inhibitors of this pathway have entered advanced stages of clinical research. This chapter intends to highlight substantial medicinal chemistry lead identification and optimization efforts that led to the discovery of key isoform-and PIK family-selective PI3K inhibitors. Coverage is given for those disclosed PI3K isoform-selective inhibitors that have entered clinical trials in oncology, regardless of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Previous studies have shown 6 to bind to tubulin at concentrations associated with high levels of PI3K inhibition (>1 μM) and for this interaction to result in cell cycle arrest in the G 2 /M phase . Other pan class I PI3K inhibitor series, as exemplified by dactolisib 9 and pictilisib 10 in Figure , lacked this activity supporting the possibility for separating the tubulin binding effects from the PI3K activity in the 2-( N -morpholino)­pyrimidine series. , The extent of tubulin binding had previously been assessed for 6 using a phenotypic screen scoring for the percentage of cells containing condensed DNA, as a way to measure cell cycle arrest in an A2058 cell line . Using this assay, compounds were screened at a fixed concentration of 5 μM to identify structure–activity relationships (SAR) that would provide a wide separation between the readout for tubulin binding and the targeted pan-PI3K potency range (class IA Rat1 cellular IC 50 ’s < 100 nM).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous studies have shown 6 to bind to tubulin at concentrations associated with high levels of PI3K inhibition (>1 μM) and for this interaction to result in cell cycle arrest in the G 2 /M phase . Other pan class I PI3K inhibitor series, as exemplified by dactolisib 9 and pictilisib 10 in Figure , lacked this activity supporting the possibility for separating the tubulin binding effects from the PI3K activity in the 2-( N -morpholino)­pyrimidine series. , The extent of tubulin binding had previously been assessed for 6 using a phenotypic screen scoring for the percentage of cells containing condensed DNA, as a way to measure cell cycle arrest in an A2058 cell line . Using this assay, compounds were screened at a fixed concentration of 5 μM to identify structure–activity relationships (SAR) that would provide a wide separation between the readout for tubulin binding and the targeted pan-PI3K potency range (class IA Rat1 cellular IC 50 ’s < 100 nM).…”
Section: Resultsmentioning
confidence: 68%
“…22,23 The extent of tubulin binding had previously been assessed for 6 using a phenotypic screen scoring for the percentage of cells containing condensed DNA, as a way to measure cell cycle arrest in an A2058 cell line. 7 Using this assay, compounds were screened at a fixed concentration of 5 μM to identify structure−activity relationships (SAR) that would provide a wide separation between the readout for tubulin binding and the targeted pan-PI3K potency range (class IA Rat1 cellular IC 50 's < 100 nM). Selected examples are included in Table 1 to highlight some of the key tubulin binding SAR, along with class IA PI3K and mTOR inhibitory activities.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small-molecule inhibitors of PI3K have been developed to target the ATP binding site in the kinase domain, since class I PI3Ks have a highly conserved ATP binding region and have similar three-dimensional structures among PI3K isoforms [ 111 ]. The ATP binding site is located between the two lobes of the kinase domain and is separated by a hinge region [ 114 ]. The structure of a small molecule mimicking the adenine ring of ATP anchors in the binding site via hydrogen bonds, leading to a disruption of enzyme activity [ 115 ].…”
Section: Current Research On Pi3k/akt/mtor Inhibitors In Lung Cancermentioning
confidence: 99%
“…The structure of a small molecule mimicking the adenine ring of ATP anchors in the binding site via hydrogen bonds, leading to a disruption of enzyme activity [ 115 ]. The presence of the hinge interaction is preserved in most PI3K inhibitors; however, the interaction of small molecules with other regions surrounding the ATP binding site, including the lower hinge, kβ3-kβ4 strands and p-loop region, also contributes to isoform selectivity [ 114 ].…”
Section: Current Research On Pi3k/akt/mtor Inhibitors In Lung Cancermentioning
confidence: 99%